Gut-derived lactic acid enhances tryptophan to 5-hydroxytryptamine in regulation of anxiety via Akkermansia muciniphila - Miaomiao Pan; Chenglang Qian; Shaoye Huo; Yuchen Wu; Xinyi Zhao; Yueming Ying; Boyu Wang; Hao Yang; Anaguli Yeerken; Tongyao Wang; Mengwei Fu; Lihong Wang; et al. (Gut Microbes)
The gut microbiota plays a pivotal role in anxiety regulation through pathways involving neurotransmitter production, immune signaling, and metabolic interactions. Among these, gut-derived serotonin (5-hydroxytryptamine, 5-HT), synthesized from tryptophan metabolism, has been identified as a key mediator. However, it remains unclear whether specific microbial factors regulate tryptophan metabolism to influence 5-HT production and anxiety regulation. In this study, we analyzed 110 athletes undergoing closed training and found that fecal lactate levels were significantly associated with anxiety indicators. We observed a significant negative correlation between Akkermansia abundance and anxiety levels in athletes. Co-supplementation with lactate and Akkermansia muciniphila (A. muciniphila) modulated tryptophan metabolism by increasing key enzyme TPH1 and reducing IDO1, thus shifting metabolism from kynurenine (Kyn) to 5-HT. In addition, lactate enhanced the propionate production capacity of A. muciniphila, potentially contributing to anxiety reduction in mice. Taken together, these findings suggest that enteric lactate and A. muciniphila collaboratively restore the imbalance in tryptophan metabolism, leading to increased 5-HT activity and alleviating anxiety phenotypes. This study highlights the intricate interplay between gut metabolites and anxiety regulation, offering potential avenues for microbiota-targeted therapeutic strategies for anxiety.